Perspectives and consensus among international orthopaedic surgeons during initial and mid-lockdown phases of coronavirus disease - Jerome, J. Terrence Jose; Mercier, Francisco; Mudgal, Chaitanya S.; Arenas-Prat, Joan; Vinagre, Gustavo; Goorens, Chul Ki; Rivera-Chavarría, Ignacio J.; Sechachalam, Sreedharan; Mofikoya, Bolaji; Thoma, Achilleas; Medina, Claudia; Ilavarasu, Tamilmani; et al. (Thieme, 2020)
With a lot of uncertainty, unclear, and frequently changing management protocols, COVID-19 has significantly impacted the orthopaedic surgical practice during this pandemic crisis. Surgeons around the world needed closed introspection, contemplation, and prospective consensual recommendations for safe surgical practice and prevention of viral contamination. One hundred orthopaedic surgeons from 50 countries were sent a Google online form with a questionnaire explicating protocols for admission, surgeries, discharge, follow-up, relevant information affecting their surgical practices, difficulties faced, and many more important issues that happened during and after the lockdown. Ten surgeons critically construed and interpreted the data to form rationale guidelines and recommendations. Of the total, hand and microsurgery surgeons (52%), trauma surgeons (32%), joint replacement surgeons (20%), and arthroscopy surgeons (14%) actively participated in the survey. Surgeons from national public health care/government college hospitals (44%) and private/semiprivate practitioners (54%) were involved in the study. Countries had lockdown started as early as January 3, 2020 with the implementation of partial or complete lifting of lockdown in few countries while writing this article. Surgeons (58%) did not stop their surgical practice or clinics but preferred only emergency cases during the lockdown. Most of the surgeons (49%) had three-fourths reduction in their total patients turn-up and the remaining cases were managed by conservative (54%) methods. There was a 50 to 75% reduction in the number of surgeries. Surgeons did perform emergency procedures without COVID-19 tests but preferred reverse transcription polymerase chain reaction (RT-PCR; 77%) and computed tomography (CT) scan chest (12%) tests for all elective surgical cases. Open fracture and emergency procedures (60%) and distal radius (55%) fractures were the most commonly performed surgeries. Surgeons preferred full personal protection equipment kits (69%) with a respirator (N95/FFP3), but in the case of unavailability, they used surgical masks and normal gowns. Regional/local anesthesia (70%) remained their choice for surgery to prevent the aerosolized risk of contaminations. Essential surgical follow-up with limited persons and visits was encouraged by 70% of the surgeons, whereas teleconsultation and telerehabilitation by 30% of the surgeons. Despite the protective equipment, one-third of the surgeons were afraid of getting infected and 56% feared of infecting their near and dear ones. Orthopaedic surgeons in private practice did face 50 to 75% financial loss and have to furlough 25% staff and 50% paramedical persons. Orthopaedics meetings were cancelled, and virtual meetings have become the preferred mode of sharing the knowledge and experiences avoiding human contacts. Staying at home, reading, and writing manuscripts became more interesting and an interesting lifestyle change is seen among the surgeons. Unanimously and without any doubt all accepted the fact that COVID-19 pandemic has reached an unprecedented level where personal hygiene, hand washing, social distancing, and safe surgical practices are the viable antidotes, and they have all slowly integrated these practices into their lives. Strict adherence to local authority recommendations and guidelines, uniform and standardized norms for admission, inpatient, and discharge, mandatory RT-PCR tests before surgery and in selective cases with CT scan chest, optimizing and regularizing the surgeries, avoiding and delaying nonemergency surgeries and follow-up protocols, use of teleconsultations cautiously, and working in close association with the World Health Organization and national health care systems will provide a conducive and safe working environment for orthopaedic surgeons and their fraternity and also will prevent the resurgence of COVID-19.